The Sociocebo, Socioebo, Or Socebo Effect - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2025)
The impact of the surrounding social ecosystem on thewellbeing of an individual is well known. Based on thisconcept in this brief article we propose a novel termcalled the socebo effect, which may be defined as thepositive impact that occurs secondary to a change in thepsychological factors associated with disease, thephysician, the person-physician interaction, and/or thepublic and its healthcare ecosystem. These socialcomforters, act as non drug interventions that help toimprove the overall health related quality of life of a givenindividual. We propose, the socebo construct needs to bestudied objectively, in both acute and chronic disease,including diabetes and obesity. Keywords: Chronic disease, nocebo, placebo,psychosocial aspects, social pharmacology